2011
DOI: 10.1001/archophthalmol.2011.65
|View full text |Cite
|
Sign up to set email alerts
|

Seroreactivity Against Aqueous-Soluble and Detergent-Soluble Retinal Proteins in Posterior Uveitis

Abstract: To characterize the seroreactivity against retinal proteins in patients with posterior uveitis, retinal disease of noninflammatory origin, and healthy controls. Methods: Patients with posterior uveitis (n =47), molecularly confirmed photoreceptor degenerations (n=11), and healthy controls (n=33) received dilated fundus examinations at the University of Iowa. Aqueous-soluble and detergent-soluble fractions of human retina were separated by gel electrophoresis and transferred to polyvinylidene fluoride membranes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…AAbs against four glycolytic enzymes: aldolase (ALDO), α-enolase (ENO1), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and pyruvate kinase M2 (PKM2) are particularly prevalent in sera of patients with autoimmune retinopathies, including cancer-associated retinopathy (CAR) and melanoma-associated retinopathy (MAR). Similar AAbs were also reported in autoimmune uveitis (22, 23). Although anti-enolase and other enzymes can be detected in low titers in some healthy individuals (from 0 to 10% depending on population studied), they were likely generated in response to common infections (18, 24).…”
Section: Introductionsupporting
confidence: 85%
“…AAbs against four glycolytic enzymes: aldolase (ALDO), α-enolase (ENO1), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and pyruvate kinase M2 (PKM2) are particularly prevalent in sera of patients with autoimmune retinopathies, including cancer-associated retinopathy (CAR) and melanoma-associated retinopathy (MAR). Similar AAbs were also reported in autoimmune uveitis (22, 23). Although anti-enolase and other enzymes can be detected in low titers in some healthy individuals (from 0 to 10% depending on population studied), they were likely generated in response to common infections (18, 24).…”
Section: Introductionsupporting
confidence: 85%
“…3 Moreover, antiretinal antibodies are detectable in an array of systemic autoimmune disorders 29,30 and retinal degenerations, 8,31 as well as in healthy controls, 9,32 suggesting that their presence is not necessarily diagnostic. It is possible that the antiretinal antibodies detectable in AIR may not be pathogenic, but rather a result of retinal damage untied to the underlying etiology.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Antiretinal antibodies have been reported in up to 42% of normal controls. 31 Proving the pathogenicity of these autoantibodies in various disease states is difficult, and requires rigorous scientific proof. A recent review has shown that to date there have been at least 17 different antiretinal antibodies described in patients with presumed AIR.…”
Section: Antiretinal Antibodies: Pathogenic Uncertaintiesmentioning
confidence: 99%